Emotional Reactivity and Dysregulation and Problematic Internet Use on Twitter - Esther Andangsari; Trisa Putri; Shavina Ghaisani; Moondore Ali; Greta Paramita; Ade Kemala (Engineering Proceedings)
Social media users can experience Problematic Internet Use (PIU) in the form of psychological problems, such as loneliness, social anxiety, and depression. They tend to have antecedents in the form of emotional dysregulation and reactivity, making them easily respond to stimuli on social media that cause stress. This study aims to prove that emotional dysregulation and reactivity are precursors of PIU for social media users. With 307 Twitter users as the participants of this study, three proposed hypotheses were tested, and the results showed that emotional dysregulation causes PIU, with emotional reactivity as a mediator.